Experimental Co-infection of Low Pathogenic Avian Influenza Virus (H9N2) and Escherichia Coli in SPF Broiler Chickens. - Mohamed Taha (South Valley University, 2019)
The work was implemented to evaluate the pathogenicity of H9N2 when co-infected with the E.coli. Avian influenza H9N2 virus strain A/chicken/Egypt/1618F/2016 which was isolated from Luxor province during 2016 and E.coli serotype O78 were used in this research. Sixty SPF birds were divided into 6 groups of ten birds each. At age 21 days, group 1 was inoculated with H9N2 only, group 2 received E.coli and three days later received H9N2, group 3 inoculated with H9N2 and after three days received E.coli, group 4 was challenged with E.coli and H9N2 at the same time, group 5 was inoculated with E.coli only, and group 6 was designed as a negative group. Clinical signs, postmortem examination, and serological examination were monitored for 15 days. The H9N2 virus presence was assessed in tracheal and cloacal swabs using real-time PCR. The most severe signs and lesions were observed in groups (3, and 4), with also high mortality rate than other groups with a percentage of 20%. Groups 3, and 4 showed a longer duration in virus shedding in the tracheal and cloacal samples. The hemagglutination inhibition test, group 4 showed high HI antibody titer against AIV-H9N2 antigen than other groups, while group 2 showed the lowest HI antibody titer against AIV-H9N2 antigen than other groups that received only the H9N2 virus. In conclusion, the outcomes of this study revealed that the infection of H9N2 with E.coli can exacerbate the clinical outcomes and mortality rates which leads to higher economic losses in chicken flocks.